Growth Response of Oil Palm Seedlings (Elaeis guineensis Jacq) to Administration of Planmate Organic Fertilizer in Main Nurseries - Defa Okta Gunawan (Central Research Institute For Agriculture, 2023)
The objective of the experiment was to determine the growth response of oil palm (Elaeis guineensis Jacq) seedlings to the application of planmate organic fertilizer in the main nursery. The experiment used a completely randomized design (CRD) with 5 treatment levels consisting of; P0 = without applying planmate fertilizer, P1 = 300 g per polybag, P2 = 350 g per polybag, P3 = 400 g per polybag, P4 = 450 g per polybag. Each treatment level was repeated 3 (three) times, so that there were experimental units, each plot consisting of 3 (three) polybags of oil palm seeds, so that a total of 45 polybags, all plants were sampled. Parameters observed were soil pH, plant height, seedling stem diameter, plant dry weight, and root dry weight. The results of the study showed that the application of planmate fertilizer had a significant effect on soil pH, plant height, stem diameter, shoot dry weight, and root dry weight. The best dose of planmate fertilizer is 450 g per polybag (P4) to give yields on shoot height, stem diameter, dry weight of plants and dry weight of roots of oil palm seedlings.